Understanding the evolution of China’s technology standard policy from 1949 to 2019 through the lens of policy learning - Song, Zhihong; Wang, Xiangping; Yan, Xinhong; Lee, Dongmei (Edelweiss Applied Science and Technology, 2024)
Understanding the evolution of Chinese technology standards policy and clarifying the pathways of policy advancement may assist in shaping and improving future technology standards policy. By extracting policy keywords from the policy text, this paper analyzes the periodical characteristics of China’s technology standard policy from 1949 to 2019 through the lens of policy learning. The findings suggest that China’s technology standards policy has evolved from "passive reaction" to "active promotion" and finally to "comprehensive domination". The technology standard policy themes develop through distinct stages, initially focusing on ensuring product quality, then shifting towards promoting the technological transformation of enterprises, and subsequently advancing to promoting the upgrading of industrial technology, followed by the formulation of technology standards with independent innovation, and finally, constructing a new system of technology standards. In addition, the endogenous learning pattern dominated the evolution of Chinese technology standard policy, while rarely showing the characteristics of an exogenous learning pattern.